Sexual double standard in friends with benefits relationships: A literature review - Marques, A. S.; Oliveira, J. M. de.; Nogueira, C. (Women's Studies International Forum, 2024)
The primary focus of this literature review is to address the complexities of friends with benefits relationships and explore underlying theories regarding the impact of sexual double standards in these relationships. The experience of women's sexuality within casual relationships is heavily influenced by gender norms and the persistence of sexual double standards. These standards subject women to negative evaluations for engaging in behaviors deemed acceptable for men. While some literature suggests that friends with benefits relationships can empower women, others highlight how sexual double standards may limit women's participation and enjoyment in these relationships. By adopting a feminist theory perspective, this literature review aims to critically assess sexual double standards in friends with benefits relationships, shedding light on both empowering and constraining aspects of these relationships. Additionally, by providing historical context and empirical data, the review allows for future research in this field to address literature gaps, attempt to deconstruct gender expectations in this non-traditional relationship, and provide theoretical support for gender equality movements.